Complementary roles in cancer prevention: protease inhibitor makes the cancer preventive peptide lunasin bioavailable. - Chia-Chien Hsieh; Blanca Hernández-Ledesma; Hyun Jin Jeong; Jae Ho Park; Ben O de Lumen (PLoS ONE, 2010)
BACKGROUND: The lower incidence of breast cancer among Asian women compared with Western countries has been partly attributed to soy in the Asian diet, leading to efforts to identify the bioactive components that are responsible. Soy Bowman Birk Inhibitor Concentrate (BBIC) is a known cancer preventive agent now in human clinical trials. METHODOLOGY/PRINCIPAL FINDINGS: The objectives of this work are to establish the presence and delineate the in vitro activity of lunasin and BBI found in BBIC, and study their bioavailability after oral administration to mice and rats. We report that lunasin and BBI are the two main bioactive ingredients of BBIC based on inhibition of foci formation, lunasin being more efficacious than BBI on an equimolar basis. BBI and soy Kunitz Trypsin Inhibitor protect lunasin from in vitro digestion with pancreatin. Oral administration of (3)H-labeled lunasin with lunasin-enriched soy results in 30% of the peptide reaching target tissues in an intact and bioactive form. In a xenograft model of nude mice transplanted with human breast cancer MDA-MB-231 cells, intraperitoneal injections of lunasin, at 20 mg/kg and 4 mg/kg body weight, decrease tumor incidence by 49% and 33%, respectively, compared with the vehicle-treated group. In contrast, injection with BBI at 20 mg/kg body weight shows no effect on tumor incidence. Tumor generation is significantly reduced with the two doses of lunasin, while BBI is ineffective. Lunasin inhibits cell proliferation and induces cell death in the breast tumor sections. CONCLUSIONS/SIGNIFICANCE: We conclude that lunasin is actually the bioactive cancer preventive agent in BBIC, and BBI simply protects lunasin from digestion when soybean and other seed foods are eaten by humans.